Manajemen Dakwah Rasulullah Dalam Menanamkan Sikap Moderasi Beragama Umat Islam di Madinah - Zakaria Zakaria (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2019)
Da'wah management is the process of planning, implementing, grouping, gathering and placing executing forces in task groups and then moving towards achieving the objectives of da'wah. Da'wah activities that are managed properly will result in successful propaganda. As the Da'wah manager, Rasulullah had implemented comprehensive Da'wah management while in Medina. One focus of the missionary management of the Prophet is to shape the attitude of religious moderation of Muslims in Medina. Religious moderation is an impartial attitude in thinking, interacting and behaving that allows it to be fair and not excessive in religion. Islam is a moderate religion (al-wasathiyah). It is a religion that teaches its people to maintain balance, uphold justice, tolerance and compassion towards others. There are four steps to preaching the Messenger of Allah during his stay in Medina, namely establishing the Prophet's Mosque as a center for worship, education, social and politics; To put between Ansar and Muhajirin in religious ties, to compile the Medina Charter which guarantees the safety of Jews and Christians; and correspondence with the authorities around Medina. To form the attitude of religious moderation of Muslims in Medina, the Messenger of Allah applied six principles of Islamic moderation, namely upholding justice, maintaining balance, instilling tolerance, avoiding extreme behavior, mastering knowledge and compassion towards others.